Under-Utilization of Women in the Labor Market of Pakistan - Mariam Sohail; Muqqadas Rehman; Chaudhary Abdul Rehman (Journal of Business & Tourism, 2021)
The aim of this study is to find out the reasons which stop the educated women form utilizing their professional skills in Pakistan.A sample of twelve females is selected, out of which six are doing jobs in different sectors of Pakistan and six are unemployed but having professional graduation and masters degrees. Interviews are conducted with the participants. Findings indicate that culture and societal behavior, parents/family, male dominancy, bad working environment, long working hours, distant jobs, conveyance, safety issues, job discrimination, disinterest, household tasks, work-life balance are the main hurdles which stopwomen from doing jobs. All respondents agree that Islam does not stop women from jobs. Mostly, women prefer teaching profession because of less time and better working environment. Economy of the Pakistan will grow if educated women start utilizing their talent in the job market.